Students’ anxiety level in learning calculus 1 during the covid-19 endemic - Razali, Fadila Amira; Dasman, Anisah; Dzulkifli, Nor Fadhilah; Mohamed, Marina; Mohammed, Norhuda (GADING Journal for the Social Sciences, 2023)
The COVID-19 pandemic has precipitated substantial modifications to the educational system, requiring students to continually switch from traditional learning into online distance learning. Previous studies have revealed that students experienced severe levels of anxiety in the COVID-19 period. Considering the close relationship that has always linked anxiety to mathematics, this paper is concerned with the anxiety level of Diploma Science students at Universiti Teknologi MARA(UiTM) Pahang(Jengka Campus)in relation to the Calculus 1 course. This study aimed to identify the anxiety level of student in learning Calculus 1 during online distance learning. Additionally, the study sought to ascertain whether there was a significant difference in the mean levels of anxiety levels and academic performance between genders. The study sample consisted of 218 Diploma in Science (AS120) students. The collected data were analyzed using mean score and independence t-test analysis. The result highlighted that three factors, emotion, environment and technology, had a low level of anxiety. Based on the mean score obtained, the students were rarely affected emotionally, environmentally, and technologically towards this course during online learning. Meanwhile, students experience more anxiety with their assessment factor in learning Calculus 1. The comparison between males and females with respect to anxiety factors and their performance in Calculus 1 has also been checked. The overall mean values for three anxiety factors of emotion, environment and assessment anxiety were slightly higher in male students as compared to female students. Moreover, female students were found to have higher performance in Calculus 1 than male students. This indicates that female students perform better in Calculus 1 during online learning compared to male students. Thus, it can be seen that anxiety level significantly affects the students‟ performance. Therefore, it is recommended that University should take action and concern towards the students and manage their academic anxiety to boost their confidence in online learning, especially in the Calculus 1 subject.